Tuberculosis Current Issues in Diagnosis and Management - Mahboub, Bassam H.; Vats, Mayank G. (IntechOpen, 2013)
Data are rapidly accumulating from all over the world regarding the efficacy of standardized treatment regimens for drug-sensitive, drug-resistant TB and latent TB infection. While we are facing the menace of multi drug-resistant TB [MDR-TB], extensively drug-resistant tuberculosis [XDR TB] has emerged threatening to undermine global efforts at TB control. Hence we have included chapters to cover all aspects of the diagnosis and management of MDR TB. This book will cover all these developments in great detail. With the widespread availability of internet globally various standard web resources available on TB have also been included so that the readers may get the comprehensive and updated guidelines from these resources. The changing clinical presentation of TB, advances in laboratory, imaging diagnostic modalities, therapeutic measures and emergence of MDR TB all suggest a pressing need to have a updated book on TB. Furthermore, while all physicians encounter the TB disease in their clinical practice, there have been a lot of controversies and misconceptions over various issues for the diagnosis and management of TB. Paucity of a well referenced, updated, standard book of TB has prompted us to undertake this venture sharing the clinical experience of global experts of TB. Our book contains chapters on epidemiology, immune-pathology, diagnosis, treatment and latest advances for TB, highlighting the global perspective of tuberculosis. World-wide resurgence of MDR TB indicates that the battle against this foe of mankind will continue in the coming years. TB still remains to be a research priority of paramount importance from medical, social and financial aspects and we have attempted to highlight all the aspects for the treatment of TB. We believe that this book will serve as a practical guide for the diagnosis and management of TB for practicing physicians (especially pulmonologists and internists) and all those who are involved in the management of TB.